2012
DOI: 10.4161/epi.20193
|View full text |Cite
|
Sign up to set email alerts
|

A distinct DNA methylation signature defines pediatric pre-B cell acute lymphoblastic leukemia

Abstract: Pre-B cell acute lymphoblastic leukemia (ALL) is the most prevalent childhood malignancy and remains one of the highest causes of childhood mortality. Despite this, the mechanisms leading to disease remain poorly understood. We asked if recurrent aberrant DNA methylation plays a role in childhood ALL and have defined a genome-scale DNA methylation profile associated with the ETV6-RUNX1 subtype of pediatric ALL. Archival bone marrow smears from 19 children collected at diagnosis and remission were used to deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 21 publications
3
44
0
Order By: Relevance
“…The utility of these samples for DNA methylation and miRNA expression analysis has been outlined previously [34,50]. Cryogenically frozen patient bone marrows were also used where available.…”
Section: Methodsmentioning
confidence: 99%
“…The utility of these samples for DNA methylation and miRNA expression analysis has been outlined previously [34,50]. Cryogenically frozen patient bone marrows were also used where available.…”
Section: Methodsmentioning
confidence: 99%
“…DNA methylation is the most robust epigenetic mark and will survive typical sample processing procedures and storage conditions. DNA methylation can be determined in histological specimens such as formalin-fixed, paraffin-embedded (FFPE) samples (Thirlwell et al 2012) and microscopic preparations (Wong et al 2012). Finally, it may reasonably be anticipated that sensitive techniques for methylation detection and quantification amenable to biomarker identification will become progressively easier and more economical to perform in the clinical setting.…”
Section: Methylation Biomarkers In Diagnosis and Prognosismentioning
confidence: 99%
“…As a biomarker in clinical oncology, DNA methylation analysis eliminates the need for expensive patient-specific genetic testing yet can robustly define disease state and direct-targeted therapeutics (5)(6)(7)(8)(9)(10). Recently, Wong et al (8 ) discovered a panel of 15 hypermethylated gene promoters associated with childhood acute lymphoblastic leukemia (ALL) 9 regardless of disease subtype and suggested that these markers may serve as molecular biomarkers for disease diagnosis and tracking.…”
mentioning
confidence: 99%
“…MALDI-TOF mass spectrometry technology is a useful and commonly used tool for measuring DNA methylation in research (8,12,13 ). Here we used synthetic DNA methylation reference materials that enabled us to determine the diagnostic thresholds and LOD of novel and established MALDI-TOF MS techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation